Genotype x environment interaction for boll weight and seed-cotton yield in asiatic cotton (Gossypium herbaceum) - PATEL, J C; PATEL, U G; MODI, D D (The Indian Journal of Agricultural Sciences, 2013)
Six promising varieties of asiatic cotton (Gossypium herbaceum L.) with 2 controls, viz 'G Cot 11' and 'Digvijay' were evaluated during 1989-90 and 1991-92 at Surat. Tile data were analysed for stability parameters, to identify the variety showing stable performance for seed-cotton yield and boll weight in a wide range of environments. Five varieties, viz '625 BB', '5529/1763', '1148 BB', '388 BK (Red)' and '2021', recorded above-average mean yield and boll weight. whereas '5529/1763' emerged as the most stable by showing regression around 1 and low deviation mean square, indicating general adaptability.